A Remark on Monge-Ampere Equations in Nonstrictly Convex Domains (Journal of Partial Differential Equations, 1996)
In this paper, we discuss the regularity of the weak solutions and the existence of the classical solutions for Monge-Ampère equations on the bounded convex domains possessing uniform parabolic support. This paper improves the conclusion of [1].
Keywords: Partial differential equation; elliptic different equation; Mange-Ampère equation; nonstrict convex domain